Effect of Amine Functionalization of MOF Adsorbents for Enhanced CO2 Capture and Separation: A Molecular Simulation Study - Bahamon, Daniel; Anlu, Wei; Builes, Santiago; Khaleel, Maryam; Vega, Lourdes F. (Frontiers in Chemistry, 2021)
Different types of amine-functionalized MOF structures were analyzed in this work using molecular simulations in order to determine their potential for post-combustion carbon dioxide capture and separation. Six amine models -of different chain lengths and degree of substitution- grafted to the unsaturated metal sites of the M2(dobdc) MOF (and its extended version, M2(dobpdc)) were evaluated, in terms of adsorption isotherms, selectivity, cyclic working capacity and regenerability. Good agreement between simulation results and available experimental data was obtained. Moreover, results show two potential structures with high cyclic working capacities if used for Temperature Swing Adsorption processes: mmen/Mg/DOBPDC and mda-Zn/DOBPDC. Among them, the -mmen functionalized structure has higher CO2 uptake and better cyclability (regenerability) for the flue gas mixtures and conditions studied. Furthermore, it is shown that more amine functional groups grafted on the MOFs and/or full functionalization of the metal centers do not lead to better CO2 separation capabilities due to steric hindrances. In addition, multiple alkyl groups bonded to the amino group yield a shift in the step-like adsorption isotherms in the larger pore structures, at a given temperature. Our calculations shed light on how functionalization can enhance gas adsorption via the cooperative chemi-physisorption mechanism of these materials, and how the materials can be tuned for desired adsorption characteristics.